75.3k views
5 votes
5. Find the general solution to y'''-y''+4y'-4y = 0

1 Answer

3 votes

For any equation,


a_ny^(n)+\dots+a_1y'+a_0y=0

assume solution of a form,
e^(yt)

Which leads to,


(e^(yt))'''-(e^(yt))''+4(e^(yt))'-4e^(yt)=0

Simplify to,


e^(yt)(y^3-y^2+4y-4)=0

Then find solutions,


\underline{y_1=1}, \underline{y_2=2i}, \underline{y_3=-2i}

For non repeated real root y, we have a form of,


y_1=c_1e^t

Following up,

For two non repeated complex roots
y_2\\eq y_3 where,


y_2=a+bi

and,


y_3=a-bi

the general solution has a form of,


y=e^(at)(c_2\cos(bt)+c_3\sin(bt))

Or in this case,


y=e^0(c_2\cos(2t)+c_3\sin(2t))

Now we just refine and get,


\boxed{y=c_1e^t+c_2\cos(2t)+c_3\sin(2t)}

Hope this helps.

r3t40

User Mike Johnson
by
5.2k points